Relationship between quality indicators and age indicators in Pennisetum purpureum cv. Cuba CT-169 in Cauto Valley, Cuba - Ram?rez, J. L.; Herrera, Rafael Segundo; Cisneros, M.; Verdecia, D.; ?lvarez, Y.; L?pez, B. (Cuban Journal of Agricultural Science, 2012)
In a random block design with four replications, quality indicators related to the climate and age of Pennisetum purpureum cv. Cuba CT-169 were determined in both seasonal periods. The experiment was carried out in a fluvisol soil, under non-irrigation conditions and without fertilization. A multivariate analysis of main components was made, considering the climatic factors and the quality indicators. The preponderance value, equal or higher than 0.75 was considered as the selection factor. Linear multiple equations and the values of the coefficient of determination were above 0.88. The highest R2 were obtained for DMD and OMD (equation II = a + b*CF +d* Age, P < 0.001). Pennisetum purpureum cv. Cuba CT-169 can be characterized by rainfall, temperature (minimum, mean, maximum) and relative humidity, also through CP, CF, ADF, L, CW, DMD, OMD, ME, FNE, CC and cellulose. Linear multiple regression equations were established between DMD, OMD, ME and FNE considering: a) CP, CC and age; b) CF, CW and age; c) CP, L and age, with high R2 and low standard errors of estimation and square mean of the error. Further studies on regrowth physiology in other varieties and types of soil are recommended. More studies mainly on the performance of the chemical composition indicators are suggested to collect more information about the climatic conditions of Cauto Valley so as to validate results in other regions of the country. Key words: Pennisetum purpureum, multivariate, multiple regressions